CAMPING THE DOCUSOAP: A QUEER FEMINIST ANALYSIS OF THE DOCUSOAP GENRE OF REALITY TELEVISION - Oberst, Clementine (My University, 2025)
This dissertation addresses the lack of critical and academic attention to queer women’s interpretive positionalities, particularly of the docusoap genre of reality television. By theorizing camp as a queer interpretive method, I explore how resistant reading strategies from a queer feminist perspective offer new ways to think about the possibilities of the docusoap and to theorize queer audiences. The genre, which focuses on the lives of wealthy women, traffics in spectacle, drama, and aesthetic excess. Using qualitative methods, I highlight some of the possible resonances of the docusoap to the lives of queer women, including the focus on homosociality, the narrative marginalization of heteronormative family structures, the denaturalization of femininity through visible gender performance, and the destabilization of the domestic space as a site of public conflict rather than private refuge. This dissertation also makes use of an audience study to provide insights on the under-researched demographic of queer women reality television audiences, revealing engaged viewers who read these texts actively and often oppositionally to create new queer meanings. My analysis combined with this audience study demonstrates the diversity and complexity of queer reading strategies, suggesting that there is no one way to understand the docusoap queerly. The application of specifically queer thought—with an intersectional approach which explicitly considers race, ethnicity, and class—to reality television studies results in vital new insights into both the political and rhetorical implications of these prominent media texts and the ways in which viewers who exist outside of the mainstream mediate these messages. My work intervenes in this field as I redress the overwhelming focus on white gay men in queer television studies. This project represents one small step in understanding how queer women interact with popular culture—a critical step in recognizing the diversity and polysemy of queer audience practices.